Zika virus alters the microRNA expression profile and elicits an RNAi response in Aedes aegypti mosquitoes. - Miguel A Saldaña; Kayvan Etebari; Charles E Hart; Steven G Widen; Thomas G Wood; Saravanan Thangamani; Sassan Asgari; Grant L Hughes (Public Library of Science (PLoS), 2017)
Zika virus (ZIKV), a flavivirus transmitted primarily by Aedes aegypti, has recently spread globally in an unprecedented fashion, yet we have a poor understanding of host-microbe interactions in this system. To gain insights into the interplay between ZIKV and the mosquito, we sequenced the small RNA profiles in ZIKV-infected and non-infected Ae. aegypti mosquitoes at 2, 7 and 14 days post-infection. ZIKA induced an RNAi response in the mosquito with virus-derived short interfering RNAs and PIWI-interacting RNAs dramatically increased in abundance post-infection. Further, we found 17 host microRNAs (miRNAs) that were modulated by ZIKV infection at all time points. Strikingly, many of these regulated miRNAs have been reported to have their expression altered by dengue and West Nile viruses, while the response was divergent from that induced by the alphavirus Chikungunya virus in mosquitoes. This suggests that conserved miRNA responses occur within mosquitoes in response to flavivirus infection. This study expands our understanding of ZIKV-vector interactions and provides potential avenues to be further investigated to target ZIKV in the mosquito host.